Effect Of Cassia Auriculata On Blood Glucose, Plasma Insulin And Hepatic Key Enzymes In Streptozotocin- Nicotinamide Induced Diabetes (Journal of Pharmaceutical Negative Results, 2022)
Cassia auriculata L. (Ceasalpiniaceae) has been used traditionally as antidiabetic and has been proven scientifically to possess high antioxidant activity and anticancer properties. In the present study, we have investigated of Tanner’s cassia Cassia auriculta flower extract (CFEt) and leaf extract (CLEt) on hepatic key metabolic enzymes of carbohydrate metabolism in streptozotocin (STZ) induced diabetic rats. The CFEt (0.45g/kg) and CLEt (0.45 g/kg) were orally administered to diabetic rats for 45 days, after which activities of hexokinase, glucose-6-phosphate dehydrogenase, glucose-6-phosphatase, fructose-1,6-bisphosphatase, sorbitol dehydrogenase in liver and glycogen content in liver and muscle were assayed. The activities of gluconeogeneic enzymes were significantly increased, whereas the activities of hexokinase, glucose-6-phosphate dehydrogenase and glycogen were significantly decreased in diabetic control rats. Both CFEt and CLEt were able to restore the altered enzyme activities to almost near normal levels. CFEt was more effective than CLEt. Our results indicate that administration of CFEt and CLEt to diabetic animals normalizes blood glucose and causes marked improvement of altered carbohydrate metabolic enzymes during diabetes. The CFEt administration showed more effective than CLEt and glibenclamide.